Classification of mangrove forest by using 1:40 000-scale aerial photographs - Ibrahim, Sulong; Hashim, Ismail (Elsevier, 1990)
This study was done to identify the species groups of mangrove forest in aerial photographs, to delineate their distribution and to quantify their coverage. Aerial photographs with a scale of 1:40 000 taken in 1983, were used to delineate mangrove forest from Kemaman to Kuantan. The study was conducted in two phases, interpretation of black-and-white panchromatic photographs, and field survey. Results show that there are three mangrove forest types, namely the Rhizophora type, the Avicennia/Sonneratia type, and the mixed-mangrove type. These can be delineated with 90% correct interpretation. An area of 2214 ha is covered by mangrove forest, of which 2% is the Avicennia/Sonneratia type, 24% the Rhizophora type and 74% the mixed-mangrove type. Avicennia/Sonneratia is found to have the highest stand density with 13 348 trees ha-1, followed by Rhizophora with 6697 and mixed-mangrove forest 1997. Thus, it can be concluded that mangrove forest can be delineated, classified and mapped by using this method of study.